2016
DOI: 10.1097/inf.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma-dependent Immunity in Bacillus Calmette-Guérin Vaccine Osteitis Survivors

Abstract: Background Inborn errors of interferon-gamma (IFN-γ) –mediated immunity underlie disseminated disease caused by Mycobacterium bovis Bacillus Calmette-Guérin (BCG) live vaccines. We hypothesized that some patients with osteitis after BCG vaccination may have an impaired IFN-γ immunity. Our aim was to investigate IL-12 and IFN-γ ex-vivo production stimulated with BCG and BCG+IFN-γ or BCG+IL-12, respectively, in BCG osteitis survivors. Methods Fresh blood samples were collected from 132 former BCG osteitis Finn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…Recently, we reported that there was no increased morbidity in chronic infections like tuberculosis or other chronic diseases in this cohort of former BCG osteitis patients. 7 Most previous studies of BCG osteitis patients from other countries have focused only on few patients, and the whole picture of BCG osteitis and its complications has remained unclear. Because of the rarity of the infection, no randomized controlled trials have been conducted to evaluate methods of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that there was no increased morbidity in chronic infections like tuberculosis or other chronic diseases in this cohort of former BCG osteitis patients. 7 Most previous studies of BCG osteitis patients from other countries have focused only on few patients, and the whole picture of BCG osteitis and its complications has remained unclear. Because of the rarity of the infection, no randomized controlled trials have been conducted to evaluate methods of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…All BCG osteitis cases were ethnic Finns, and this homogeneity is a benefit in genetic studies. Originally, the total number of BCG osteitis patients was 222, and as published recently, none of them had died of tuberculosis, BCG infection or other severe infection 10 . Thus, the present sample of 130 former BCG patients probably represents well the original BCG osteitis patients at the time when BCG vaccination was offered to all Finnish newborns.…”
Section: Discussionmentioning
confidence: 99%
“…BCG osteitis was more common in Finland than elsewhere at the time when BCG vaccinations were given to all Finnish newborns. During the years 1960–1988, altogether 222 children suffered from BCG osteitis in infancy 7 , 8 , and in 2008–2009, we collected questionnaire data from 160 of them and blood samples from 132 of them for immunological and genetic studies 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…They answered a questionnaire that comprised questions on chronic illnesses, long‐term medication, repeated or chronic infections and mycobacterial infections. Whole‐blood samples from 132 of the patients, who lived all over Finland, were sent to the laboratory of the National Institute for Health and Welfare, Turku, Finland . Deoxyribonucleic acid (DNA) was isolated from 200 μ L of whole blood and both DNA and serum samples were frozen at −70°C for further analyses.…”
Section: Methodsmentioning
confidence: 99%